THE ONLINE TEACHING VIS-À-VIS THE CLASSROOM TEACHING (ON THE BACKGROUND OF COVID-19) - Tvaltvadze, Darejan; Gvelesiani, Irina (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
The history of mankind will depict 2020 as the beginning of the new era – the era of the pandemic, which has invaded the world countries. The life on the earth has changed drastically. A partial or complete lockdown, numerous infected citizens, an increasing economic crisis, devaluation of a national currency, paralyzed cultural and social lives – this is a partial list of the challenges faced by the majority of the world countries that have made efforts to survive. The paper depicts the challenges of Georgia’s educational space in the environment of the pandemic. The major emphasis is put on the transition from a classroom teaching to an online lecturing as well as on the (dis)advantages of a face-to-face interaction and a virtual communication. Moreover, the paper presents some strategies of the “peaceful” transition (creation of a student-oriented virtual-classroom atmosphere, timely informativeness, usage of appropriate technological means, replacement of written-type exams with hybrid-type examinations, flexible site-oriented means of an extracurricular communication, updated criteria of assessment, etc.) elaborated at the Faculty of Humanities of Ivane Javakhishvili Tbilisi State University. The methodology of research includes observation, analysis and evaluation of the recent processes.